Analysis of Determinants of Job Stress in Nurses Throughout Indonesia: Literature - Dany, Cut Nasywa Kesuma; Octavelia, Anggi Tri; Adinda, Faiza; Aldona, Cindy; Purba, Sri Hajijah (PROMOTOR, 2024)
Work stress is matter Which certainly experienced time works especially Of nurse that Where from Indonesian National Nurses Association, 50.9% of Indonesian nurses Which work experiences work stress. in This is what this research aims to do make know what the determinants are Which result work stress on nurse on Indonesia. Method Which used in the form of a literature study that obtained from research articles through a comprehensive search Which indexed similar Publish or Perish, Google Scholar, PubMed, and several other official sites originate period time 2021-2024. results study show that There is 7 determine Which hypnotizing work stress Of nurses, namely workload, work shifts, age, work fatigue, work environment, gender, and working time. conclusion on this research is determine that most generally mastered be found on work load Which experienced by nurse as a result this will have an impact Of the health of the nurses is good physically Also mental rather Also impact on quality of service quality. sang reason that, the provider should Can increase quality of the work environment for nurses, reducing workload, as well as have method make managing work stress Of nurse so that later the nurses capable convey health services Which the best as well as quality.